Densità imprenditoriale, specializzazione settoriale e nascita di nuove imprese - Del Bosco, Barbara (Piccola Impresa / Small Business, 2014)
The paper analyses the link between start-up activity and existing local entrepreneurship,starting from a review of the literature on the agglomeration of entrepreneurial initiatives. The paper presents an empirical analysis of new ventures created in Italian provinces between 1998 and 2008. The analysis is focused on the relationship between start-up rates and previous entrepreneurship (analyzed in terms of both stock of existing firms and past start-up rates) and the relationship between the distribution of the new firms among differentindustries and the initial industrial specialization of the area. Results show persistence inlocal start-up rates, as well as a tendency of new venture creation processes to replicate theexisting industrial specialization pattern